Pengembangan Sistem Pembayaran Menggunakan Model Prototype pada SMK Mandala Bhakti Surakarta - Moh. Muhtarom; Fajar Suryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
Progress of a business activity, especially in the field of finance at educational institutions, can be seen from the financial statements of educational institutions. Financial information in the world of education also plays an important role in addition to the quality or quality of education produced in an educational institution itself. To know the condition of an institution's treasures or finances, it is necessary to make periodic financial reports. This research has purpose to develop information system of student payment by using prototype model and also implement information system of student payment at SMK Mandala Bhakti Surakarta. The description of the research that is carried out is problem identification, problem analysis, needs analysis, and the design of student payment information system. System design using Data Flow Diagram (DFD) and programming language used is Visual FoxPro 9.0. This research will produce a prototype of student payment information system at SMK Mandala Bhakti which includes student data processing, SPP payment, payment per class, transaction data, and print recap of payment in the form of certain reports.